R-Spondin3 is associated with basal-progenitor behavior in normal and tumor mammary cells - Tocci, Johanna Melisa (2018)
R-spondin3 (RSPO3) is a member of a family of secreted proteins that enhance Wnt signaling pathways in diverse processes, including cancer. However, the role of RSPO3 in mammary gland and breast cancer development remains unclear. In this study, we show that RSPO3 is expressed in the basal stem cell–enriched compartment of normal mouse mammary glands but is absent from committed mature luminal cells in which exogenous RSPO3 impairs lactogenic differentiation. RSPO3 knockdown in basal-like mouse mammary tumor cells reduced canonical Wnt signaling, epithelial-to-mesenchymal transition-like features, migration capacity, and tumor formation in vivo. Conversely, RSPO3 overexpression, which was associated with some LGR and RUNX factors, highly correlated with the basal-like subtype among patients with breast cancer. Thus, we identified RSPO3 as a novel key modulator of breast cancer development and a potential target for treatment of basal-like breast cancers. Significance: These findings identify RSPO3 as a potential therapetuic target in basal-like breast cancers. Graphical Abstract: http://cancerres.aacrjournals.org/content/canres/78/16/4497/F1.large.jpg.